The Role and Strategy of Village Government in Developing Tourism Villages Based on Local Potential - Wasdi, Wasdi (Sean Institute, 2025)
This study aims to analyze the role and strategies employed by village governments in developing tourism villages based on local potential. The background of this research is based on the importance of empowering the natural, cultural, and social resources of village communities as an effort to improve economic welfare and preserve local wisdom values. The research method used was qualitative with a descriptive approach, through a literature review. The results indicate that village governments play a crucial role in developing tourism villages based on local potential, acting as facilitators, organizers, innovators, coordinators, and drivers of community empowerment. Through various strategies such as identifying local potential, establishing tourism groups (Pokdarwis), improving facilities and infrastructure, promoting tourism, strengthening community capacity, and developing targeted policies and budgets, villages are able to create attractive, competitive, and sustainable tourism destinations. This study also found that the success of tourism village development is greatly influenced by the level of community participation and the village government's ability to manage resources transparently and collaboratively.